To the question of the methodic of universities’ scientific potential appreciation - D. Znamenskiy (Управление)
The development issues of the scientific potential of higher education as an important component of the national scientific and technological system of any country has been considered. The main purpose of the study is to develop, substantiate and test methods for assessing the scientific potential of universities. The main method of research is a system-dynamic approach to the study of scientific potential.The concept of “scientific potential of higher education” has been clarified. It seems reasonable, that the modern mission of higher education, both in Russia and in the world, is to create and further develop a unified high-level educational system, capable not only of training personnel for certain sectors of the real sector of the economy, but also to produce new knowledge, i.e. to ensure high-quality scientific and technological progress in these sectors.An original method of assessing the scientific potential of higher education has been developed, and its approbation is the main empirical result of the study. The essence of this method lies in the consistent estimation of factors of formation of the scientific potential (initial assessment) and the forms of its realization (secondary assessment), and also in the comparison of the indices of the secondary and primary evaluations (summative evaluation). The obtained results allow us to develop a strategy for the development of scientific potential, depending on the level of effectiveness of its implementation.The applied value of the research results is determined by the prospects of their application in the process of development of state policy for the development of research activities in higher education. In addition, the proposed methodology can be used by University leaders, who have set themselves the goal of building scientific capacity and integration into the national scientific and technological system and international scientific cooperation.